Pyrolyzed sludge-based carbon-like powder additive for wireless power transmission - Jevoncia, Bryan (Nanyang Technological University, 2021)
Global production of sludge has reached over 20 million tonnes. In Singapore alone, a total of 250,000 tonnes of sludge was generated in 2020 and only 10% was recycled, while the rest would undergo conventional disposal practices like landfilling and incineration. Pyrolysis of the dewatered municipal sludge is an alternative disposal method to reduce the detrimental effect on environment and also the volume of waste disposed. The black carbon-like powder produced at the end of pyrolysis of sludge has an inherently complex composition as it is originated from waste and should be thoroughly studied before land filling or using in other applications like activated carbon and biochar. To explore the potential applications and usability of carbon additive, this project takes the direction that has not been examined in the literature. This project aims to evaluate its magnetic properties, identify strategies to improve the magnetic properties of the sludge-based carbon-like powder, as well as to introduce its potential application in wireless power transmission by incorporating it into transformer cores. The fabricated transformer core attained a flux density of 54.5 mT and a relative differential permeability as high as 73.4 with 90% weight fraction of carbon-like powder inclusion.